Enhance the delineation of masked structures in southern Iraq by applying the Biharmonic operator to their gravity field. - Al-Rahim, Ali M. (Iraqi Journal of Science, 2022)
The gravity field of southern Iraq shows steep gradient of regional trend. The gravity contours over the anticline structures in this area do not show the closure characteristic of these structures. The effect of lateral density variation for Hormuz Salt complicates the case in the area. Higher derivatives are one of the means that have been used to remove the effect of such regional gravity variations, which can easily mask significant structures. Biharmonic Operator is used to delineate these distort structures, follow their extent and at the same time distinguish new features. The Biharmonic operator manipulation has ability to suppress the effect of regional and enhance the local anomalies. The problem with higher derivatives operation is that, it enhance dramatically high frequency components of gravity field, but with smoothing the result is remarkable. A synthetic model is used to support the idea, and then the operation is applied to the gravity field of southern Iraq. Many new features are deduced and new extents of the old known ones are determined.